Halloween In The Orchard - Alsdurf, Phyllis, 1950-; Hunt, Lisa 1973- (Lisa Jane) (Minneapolis, MN : Beaming Books, 2023)
"A heartfelt story about enjoying Halloween and fall at the local apple orchard"--.
new kids book 2023 fall.
Ages 4-7.
Keywords: Orchards -- Fiction; Halloween -- Fiction; Picture books